In Our Midst - Classmate Magazine; Freeman, Marion; Holm, Angela (Monterey, California: Naval Postgraduate School, 2018)
Originally published in The Classmate Magazine (1961-2001), initially a publication of the Naval Postgraduate School's Officer Students' Wives' Club.